Multi-Scenario Forecasting of Land Use and Ecosystem Service Values in Coastal Regions: A Case Study of the Chaoshan Area, China - Zili Xiong; Song Yao; Hongmei Liu; Liang Yu (ISPRS International Journal of Geo-Information)
Modeling changes in ecosystem service value (ESV) resulting from land use/cover change (LUCC) in coastal regions play a crucial role in promoting regional sustainability and guiding policymaking. This study focuses on the Chaoshan region of China and analyzes the impact of land use changes in 2000, 2010, and 2020 on ESV. The Patch-generating Land Use Simulation (PLUS) model was used to simulate LUCC for 2030 under three different scenarios: natural development (ND), urban development (UD), and ecological protection (EP). The spatial distribution and aggregation degree of ESV were assessed to explore the intrinsic relationship between land use and ecosystem service value in the Chaoshan region. The results showed the following: (1) The cropland area in the Chaoshan region has significantly decreased, with the per capita cropland area dropping to 113.34 m2 (0.028 acres) by 2020. The continuous expansion of construction land has been mainly concentrated in Shantou, Jieyang, and Chaozhou, with an increasingly evident trend of urban integration among these three cities. By 2030, the growth rate of construction land in the EP scenario is expected to decline, indicating a slowdown in urban expansion. (2) Between 2000 and 2020, Shantou was the only city in the region to experience a decline in total ESV. Low ESV values in the Chaoshan region are primarily concentrated in the southeastern area. As urban integration progresses, ESV values in this region are expected to continue to decline. (3) The ongoing trend of urban integration between Shantou, Chaozhou, and Jieyang may result in the region becoming an ecologically vulnerable area. Close monitoring of potential ecological risks in this area is crucial to ensure a balance between urban development and ecological protection. This study will provide important guidance for land use policies and sustainable development in the Chaoshan region, as well as in similar coastal cities globally.